Impact of Microgravity on Cytoskeletal Dynamics, Protein Transport, and Signaling Networks: Potential Therapeutic Opportunities for Skin Health - Jamison M. Ballard; Rishitha Chiguru; Matthew B. Deeb; Rebecca B. Swatsburg; Ada Y. Lau; Grace H. Davis; Mevlana Demiri; Jewelia T. Keller; Beder Nourachi; Tasnim A. Abu Shihadeh; Rylin Schneider; Ericka Articulo; et al. (International Journal of Molecular Sciences, 2026)
Astronauts encounter several challenges on spaceflight missions, including space radiation and microgravity. Over the past several decades, studies conducted in the field of space medicine have uncovered broad impacts on human physiology, including the integumentary system, which serves as a protective barrier to environmental factors. Dermatological alterations in astronauts are commonly observed during spaceflight missions. Advancing our understanding of the intracellular mechanisms impacted in skin within the context of microgravity may uncover potential therapies for maintaining and improving skin health. Towards this goal, we utilized PubMed to survey current findings relevant to microgravity effects on cytoskeletal components, intracellular protein trafficking, and signaling cascades in mammalian model systems, in addition to identifying gaps in current knowledge. Concurrently across these studies, we focused on the specific cell culture technologies that were utilized during spaceflight missions and in microgravity simulated conditions. Altogether, we envision that these mechanistic insights will contribute to a better understanding of skin disorders such as atopic dermatitis and psoriasis, for which current treatment regimens are associated with adverse responses. Furthermore, the identified knowledge gaps will unveil new avenues for future spaceflight research to further propel scientific advancements in the field of space medicine.